A Critical Review on the Book Fundamentals of Political Economy - Gholamreza Mesbahi Moghaddam (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to evaluate the book entitled” Fundamentals of Political Economy”, which is presented from a Marxist point of view. The method of study is documentary and analytical. The result of the study is that the views of the work are criticized in terms of the production of material wealth, income distribution due to the ownership of the means of production, historical materialism, mode and relation of production, views on the laws of society, primitive man, language, labor theory of value, embodied labor, socially necessary labor time, money as a measure of value, surplus value, capitalist society, capital as the social relation of production, surplus labor, the fundamental contradiction of the capitalist system, the accumulation of capital and the deterioration of the conditions of workers and the industrial reserve army, land rent and large-scale production.